Ideas, institutional change, crisis and pandemics - Krause, Martin (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2020)
The recent crisis yielded by the Covid-19 pandemic has brought up many immediate concerns, as well as uncertainty regarding the social effects it may have in the future. Will there be institutional change in our societies? In what direction: towards a greater degree of freedom or further advancement of the role of the State? In this article, we will seek to analyze how this institutional change is devised, focusing our attention on the role played by the mainstream ideas and values in society, and how they evolve. Particularly, we will consider the role of ideas using a market as a benchmark, in which we find parties who demand and who offer, highlighting the role played by entrepreneurs. We will also see what happens when a crisis is triggered, and to what extent it impacts both the size of the market and the future path that society may follow. It is too early to say, right now, which way the market of ideas will lean after the pandemic, but we will analyze what may be the impact of the crisis, of the possible solutions, their results, and their effect on the prevailing ideas.